VARIAÇÃO INTRAESPECÍFICA DA COMPOSIÇÃO CUTICULAR EM CASTAS DE CUPINS Cornitermes cumulans - AKAMINE, Vivian; LIMA, Juliana; MICHELUTTI, Kamylla; ANTONIALLI-JUNIOR, William; CARDOSO, Claudia Andrea Lima (ANAIS DO ENIC, 2017)
-